2011
DOI: 10.1080/13691058.2011.587894
|View full text |Cite
|
Sign up to set email alerts
|

The bumpy road to socialise nature: sex education in Japan

Abstract: This study was prompted by an empirical puzzle: why is sex education in schools so underdeveloped in Japan compared to many other industrialised societies? On the one hand, formal pedagogy under state policy is conservative, emphasising reproductive and prophylactic purposes rather than a comprehensive understanding of sexuality. On the other hand, however, Japan has a highly visible sexual environment where a variety of commercial sex activities are tolerated and even encouraged. The aim of the paper is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In Japan, research related to sexual matters is limited. We believe this limitation stems from the fact that sexual topics are often considered taboo with Japanese education institutions, and sexual education in Japan lags behind that in Western countries (22)(23)(24). Additionally, the understanding of obtaining sexual consent, which is essential in all sexual activities, lags behind compared to countries that are known to be advanced in sex education in some of Europe countries (13,22,25).…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, research related to sexual matters is limited. We believe this limitation stems from the fact that sexual topics are often considered taboo with Japanese education institutions, and sexual education in Japan lags behind that in Western countries (22)(23)(24). Additionally, the understanding of obtaining sexual consent, which is essential in all sexual activities, lags behind compared to countries that are known to be advanced in sex education in some of Europe countries (13,22,25).…”
Section: Resultsmentioning
confidence: 99%
“…Although this may be one of the reasons for the low rate of permanent contraception in Japanese women, previous studies also showed that counseling on permanent contraception by healthcare providers to women in the United States 21 and the Netherlands 11 was inadequate. Another possible reason for the low rate of permanent contraception is inadequate sex education in Japan 22 . The rate of reliable contraceptive use is lower in Japan than in other countries 4 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Matsumoto et al, the little response the "pill" meets despite its introduction as a legal contraceptive in Japan in 1999 is attributed partly to the incurring costs [15,16,17]. Another reason for the lack of acceptance of the "pill" in Japan might be the approach to sex education in schools: According to Fu it is underdeveloped compared to many other industrialised societies [18]. In contrast, there is a widespread use of the combined oral contraceptive pill in Germany and Hungary.…”
Section: Discussionmentioning
confidence: 99%